2019
DOI: 10.3390/ma12182868
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Process Parameters on Microstructure and Mechanical Properties of Stainless Steel/Carbon Steel Clad Rebar

Abstract: In this study, a 304/20MnSi stainless-steel clad rebar was prepared by single-pass compression process using the MMS-200 Thermal Mechanical Simulator. The impact of different degrees of deformation and deformation temperature on microstructure evolution and the mechanical properties of stainless steel clad rebars were investigated. The study indicated that with the increase of the degree of deformation, the content of pearlite in a carbon steel matrix was increased, and the grains refined. The metallurgical bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…As the distance from carbon steel increased, the carbon content decreased so that the duplex phase of ferrite and martensite was formed. Feng et al reported that the composite rebar, the core of which was 20 MnSi and the cladding metal was 304 stainless steel, heterogeneous phases containing bainite phase were formed at the interface due to diffusion [24]. Figure 6b expounds hardness distribution that is measured from the carbon steel side to the stainless steel side.…”
Section: Interface Microstructure Of the Ssc Rebarmentioning
confidence: 99%
“…As the distance from carbon steel increased, the carbon content decreased so that the duplex phase of ferrite and martensite was formed. Feng et al reported that the composite rebar, the core of which was 20 MnSi and the cladding metal was 304 stainless steel, heterogeneous phases containing bainite phase were formed at the interface due to diffusion [24]. Figure 6b expounds hardness distribution that is measured from the carbon steel side to the stainless steel side.…”
Section: Interface Microstructure Of the Ssc Rebarmentioning
confidence: 99%
“…However, this process was limited by certain issues, such as the uneven distribution of the stainless steel cladding and the difficulty of engaging the rolling mill. Feng et al [ 17 ] used a thermal simulator to prepare 20MnSi/306L rebars with different compression temperatures (950 °C and 1050 °C) and compression rates (50% and 70%). When the compression rate increased from 50% to 70%, the number of oxides on the composite interface significantly decreased, the grains became continuously thinner, and the tensile strength of the rebar increased from 589 MPa to 690 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al simulated the rolling process of clad rebars in the laboratory using a thermal simulator and a specific fixture. When the deformation was increased from 50% to 70%, all of the properties of the bars were improved [ 15 ]. Liu et al prepared 9Cr18MoV/Cr13 clad rebars using a liquid–solid continuous casting method.…”
Section: Introductionmentioning
confidence: 99%